Features of the stress field at the surface of a flush shrink-fit shaft - Paynter, R; Hills, D; Barber, JR (2009)
The state of stress induced by a shrink-fitted circular shaft in an elastically similar half-space, positioned so that the end of the shaft is flush with the remainder of the free surface, is studied. At deep interior points the classical plane strain (Lamé) solution obtains, and the transition to the free surface state is found. It is found that a residual interfacial axial shear develops and the coefficient of friction needed to ensure adhesion along the interface is found. The effect of slip when a lower coefficient of friction is present is also found as a solution to an integral equation. JMES1403 © IMechE 2009.